A retrospective analysis on progressive ectopic pregnancy: incidence, clinical features, diagnosis, and treatment approaches - Valeryevna, Khvorik Natalya; Kolhar, Pallavi Vivekanand; Don, Niwnhalla Appuhamilage; Nimna, Denuwani; Singalaxana, Thehani Shireen; Ranasinghe, Hasini Sandeepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Progressive ectopic pregnancy is a pregnancy that develops outside the uterus which progresses if not treated promptly. Methods: A retrospective analysis of 51 patients was done in the gynecology department of Grodno State Medical university, first aid hospital. Results: According to the analysis of the obtained data, the article shows the comparison and differences of these ectopic pregnancies in different age categories, with the parity and the complications followed due to this. The percentages are as follows; women with ectopic pregnancy of <30 years=52.9%, >30 years=47%, women with ectopic pregnancy in their 1st pregnancy =13.7%, 2nd pregnancy = 45.09%, 3rd pregnancy = 33.33%, recurrence rate = 13.72%, abortion = 15.68%, miscarriage due to ectopic pregnancy= 1.96%. Prominent complaints were pain together with the presence of spotting. Among patients undergoing culdocentesis, 25.49% presented with hemorrhagic fluid, while 43.13% showed a mixed-type fluid. Within 5 days of admission, beta-hCG levels increased in 83.34% of patients and decreased in 16.66%. All patients in our retrospective study underwent tubotubal anastomosis. Out of them, 17.64% of women had a previous history of tubectomy. Conclusions: Women below 30 years with ectopic pregnancy had a higher incidence. Early diagnosis is the key to reduce the morbidity, mortality, to reduce the complications and to estimate the progression. Beta HCG level with transvaginal ultrasound (TVUS) is a preferred combination used nowadays for early diagnosis of the disease and complications such as rupture of a tubal pregnancy. To preserve fertility tubotubal anastomosis was the preferred mode of treatment (especially in patients with previous tubectomy surgery).